Binder‐Free ZnO Cathode synthesized via ALD by Direct Growth of Hierarchical ZnO Nanostructure on Current Collector for High‐Performance Rechargeable Aluminium‐Ion Batteries. Issue 44 (28th November 2018) - Pal, Dipayan; Mathur, Aakash; Singh, Ajaib; Pakhira, Srimanta; Singh, Rinki; Chattopadhyay, Sudeshna
Abstract: Nanoscale ZnO, directly grown on current collector through ALD, shows high electrochemical performance as a binder‐free cathode for rechargeable Al‐ion batteries (AIBs). Al coin cell fabricated using binder‐free ALD grown ZnO cathode (ZnO‐ALD‐E) manifests an initial discharge capacity of 2563 mAh g ‐1, and remains at 245 mAh g ‐1 at a current rate of 400 mA g ‐1 after 50 cycles with almost 95% Coulombic efficiency. Distinct and consistent plateaus in discharge/charge curves reveal the Al‐ion insertion/extraction process and electrochemical stability of the battery. The delivered discharge capacity of the battery with ZnO‐ALD‐E cathode is significantly higher (1000%) than that of batteries fabricated using a conventional ZnO cathode composed of ZnO powder (nanoparticles or bulk) and binder with conductive carbon. Ex‐situ XRD and Photoluminescence spectroscopy in different discharge/charge states of Al/ZnO‐ALD‐E battery reveal the structural information of ZnO‐ALD‐E, upon Al‐ion intercalation/deintercalation. Such remarkable electrochemical performance is attributed to the binder‐free, well‐defined textured nanostructures of ALD grown ZnO cathode with c‐axis orientation along the surface normal, facilitating good electrical contact and enhanced pathways for electron/ion transfer/transport kinetics. First principle based DFT calculations explain the Al‐ion intercalation phenomena in the framework of c‐axis oriented ZnO. The proposed concept provides a strategy for transitioning to next‐generation AIBs with a binder‐free cathode. Abstract : Excellent performance of a novel binder‐free thin ZnO film cathode, directly grown on current collector by near room temperature atomic layer deposition, is investigated in rechargeable Al‐ion battery application. ALD grown c‐axis oriented textured ZnO cathode yields significantly high specific capacity, about 1000% higher than cathodes composed of commercially available ZnO bulk powder/ nanoparticles with binder, in Al‐ion battery.